Tefl educational principles: a proposal for changing times - Bonilla Medina, Ximena (Colombian Applied Linguistics Journal, 2012)
Today’s society is influenced by new information technologies, which cause important sociological changes that impact education. As such, the field of EFL today demands different abilities and attitudes from teachers. This paper has two objectives: first, to initiate a reflection on the EFL teachers’ role, taking as an assumption that teachers have been influenced by cultural background experiences in their professional development and that this has caused them to develop a narrow view of ideal methods which may not be appealing for situations, and second, to propose three principles in foreign language teaching that will allow seeing EFL tasks from a wider view: 1) evaluating what comes from one’s cultural background that conforms to a general understanding of what teaching is, 2) re-shaping the teachers’ role in order to align with society’s demands and 3) assuming a dialogic process to building classroom strategies for language teaching and learning.